Designing a Proposed Apparatus For Developing Concentration and Shifting Attention In Throwing Events Referees - Jasim, Osn (Journal of Physical Education, 2016)
The importance of the research lies in studying the psychological factors and mental abilities related to concentration and shifting concentration in throwing events. The researchers designed an apparatus for specifying and diagnosing decision making weak points and concentration weaknesses. The aims of the research was to design an apparatus for shifting attention and developing concentration of athletics referees especially those of throwing events as well as designing exercises using the proposed apparatuses and finding their effects. The researchers hypothesized statistical differences between pre and posttests in attention shifting and concentration. The researchers used the experimental method on 10 referees from total 90 athletics referees. Bourdon attention test was used to measure concentration and attention shifting. The recommended the necessity of developing concentration and attention shifting apparatus as well as designing training programs for athletics referees. Finally they recommended making similar studies on other variables to apply on the same apparatus.